2018
DOI: 10.3390/ijerph15020278
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Common Mental Disorders in Employees. Perspectives on Collaboration from Three Health Care Professions

Abstract: Collaboration among occupational health physicians, primary care physicians and psychotherapists in the prevention and treatment of common mental disorders in employees has been scarcely researched. To identify potential for improvement, these professions were surveyed in Baden-Württemberg (Germany). Four hundred and fifty occupational health physicians, 1000 primary care physicians and 700 resident medical and psychological psychotherapists received a standardized questionnaire about their experiences, attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
2
16
0
6
Order By: Relevance
“…Obwohl der Arbeitsplatzbezug in der Sozialanamnese bei jedem psychosomatisch-psychiatrisch-psychotherapeutischen Erstkontakt Eingang finden könnte, wird dies von Therapeuten und Ärzten meist wenig ausreichend thematisiert [42]. Oft fehlt der direkte Kontakt zu innerbetrieblichen Akteuren [18] und/oder detailliertes Wissen zu Inhalten und Abläufen am jeweiligen Arbeitsplatz [42,43]. Aus diesem Grund kann davon ausgegangen werden, dass die größere Zufriedenheit der Nutzer im Betrieb der maßgeschneiderten Dienstleistungsqualität geschuldet ist.…”
Section: Dienstleistungsqualität Und Zufriedenheitunclassified
See 1 more Smart Citation
“…Obwohl der Arbeitsplatzbezug in der Sozialanamnese bei jedem psychosomatisch-psychiatrisch-psychotherapeutischen Erstkontakt Eingang finden könnte, wird dies von Therapeuten und Ärzten meist wenig ausreichend thematisiert [42]. Oft fehlt der direkte Kontakt zu innerbetrieblichen Akteuren [18] und/oder detailliertes Wissen zu Inhalten und Abläufen am jeweiligen Arbeitsplatz [42,43]. Aus diesem Grund kann davon ausgegangen werden, dass die größere Zufriedenheit der Nutzer im Betrieb der maßgeschneiderten Dienstleistungsqualität geschuldet ist.…”
Section: Dienstleistungsqualität Und Zufriedenheitunclassified
“…Der Arbeitsplatz gewinnt in der Früherkennung und Frühbehandlung an Bedeutung [15][16][17][18], da Kennzeichen seelischer Belastungen und unspezifische chronische Stressbeschwerden hier in einem frühen Stadium auffällig werden können [19].…”
Section: Introductionunclassified
“…Additionally, the representative for employees with disabilities or members from private social networks (e.g., family members, friends) can be included if the returnee wishes this support [ 8 ]. Previous research has suggested though that the cooperation of these different professions and stakeholders to achieve a successful RTW has been suboptimal so far [ 9 , 10 , 11 ]. While collaboration among different stakeholders is considered important by members of the different professions themselves, it is rarely effectively implemented in practice and needs to be extended [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Untersuchungen hinsichtlich des Behandlungsverlaufes legen nahe, dass die Früherkennung und somit auch die frühe Behandlung von psychischen Erkrankungen positive Auswirkungen auf die Prognose hat [6][7][8]. Gerade im täglichen Arbeitsumfeld können Belastungssymptome und Stressreaktionen in einem frühen Stadium auffällig werden [9], was den Arbeitsplatz für die Früherkennung daher immer wichtiger macht [10][11][12][13].…”
Section: Introductionunclassified